THE EFFECTIVENESS OF SHARIA MICROFINANCE INSTITUTIONS IN PROMOTING ECONOMIC INCLUSION FOR SMES - Ahmadi Ahmadi; Ali Khan; Fatima Malik (Yayasan Adra Karima Hubbi, 2026)
Small and Medium Enterprises (SMEs) play a crucial role in economic growth, employment creation, and poverty reduction; however, many continue to face financial exclusion due to limited access to formal financial services. Conventional financial institutions frequently impose collateral requirements and lending conditions that restrict financing opportunities for small business owners. Sharia Microfinance Institutions (SMFIs) have emerged as alternative financial intermediaries that provide Sharia-compliant financing and developmental support aimed at enhancing economic inclusion. This study aims to evaluate the effectiveness of Sharia Microfinance Institutions in promoting economic inclusion among SMEs and to examine the factors that influence inclusion outcomes. A quantitative research design was employed involving 400 SME owners who participated in Sharia microfinance programs. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling (SEM). Findings indicate that access to Sharia financing, institutional trust, financial literacy support, and business development assistance significantly contribute to economic inclusion. Access to Sharia-compliant financing emerged as the strongest predictor of inclusion, while non-financial services such as entrepreneurial training and financial education enhanced the effectiveness of financing interventions. Increased participation in Sharia microfinance programs was associated with improved financial access, business expansion, income growth, and entrepreneurial empowerment. The study concludes that Sharia Microfinance Institutions function as comprehensive development partners that promote sustainable economic inclusion through the integration of ethical financing principles, capacity building, and business support services for SMEs.